Endoscopic diagnosis of infection - Eun Jeong Gong; Kyoungwon Jung (Kosin Medical Journal)
Accurate prediction of Helicobacter pylori infection status based on endoscopic findings is essential for optimizing management. This review emphasizes the importance of accurate endoscopic diagnosis of H. pylori infection. The endoscopic findings categorized in the Kyoto classification provide valuable indicators of infection status. Specifically, findings such as atrophic gastritis, intestinal metaplasia, nodular gastritis, enlarged folds, sticky mucus, xanthoma, and map-like redness are associated with H. pylori infection. Regular arrangement of collecting venules and linear red streaks are reliable indicators of non-infection. Selective testing based on endoscopic findings can optimize diagnosis and treatment of H. pylori infection and minimize unnecessary procedures. However, some findings overlap and do not clearly distinguish between current and past infections, indicating a need for further research.